Muon collider probes of Majorana neutrino dipole moments and masses - Michele Frigerio; Natascia Vignaroli (Journal of High Energy Physics)
Abstract Majorana neutrinos may have transitional dipole moments, which violate lepton number as well as lepton flavour. We estimate the sensitivity of future colliders to the electron-muon neutrino dipole moment, λ eμ , by considering same-sign dilepton final states. We find that hadron colliders, even the proposed FCC-hh, are sensitive only to |λ eμ | ≳ 10−9 μ B (with μ B the Bohr magneton), a value two-three orders of magnitude larger than current bounds from astrophysics and low-energy neutrino-scattering experiments. In the case of a future muon collider, we show that the sensitivity varies from |λ eμ | ~ 5 ∙ 10−9 μ B for energy s $$ \sqrt{s} $$ ≃ 3 TeV, to ∼ 10 −12 μ B for s $$ \sqrt{s} $$ ≃ 50 TeV, matching the current laboratory bounds for s $$ \sqrt{s} $$ ≃ 30 TeV. The singular advantage of the muon collider signal would be a direct, clean identification of lepton number and flavour violation. We also show that a muon collider would improve by orders of magnitude the direct bounds on m eμ and m μμ , two of the entries of the Majorana neutrino mass matrix. These bounds could be as strong as ∼ 50 keV, still far above the neutrino mass scale.